MOTIVASI BERPRESTASI SISWA YANG BERPACARAN DI SMP N 7 TANAH PUTIH TAHUN AJARAN 2013/2014 - Jondri, Rovisal Jondri Rovisal; Asyari, Abu Asyari Abu; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstractTitle Research : Picture Motivate to have student achievement which have an affair [in] SMP N 7 White Land;Ground [of] School Year 2013 / 2014 ( By Rovisal Jondri, this [of] NIM 1205188188) this research intention is to know picture Motivate to have student achievement which have an affair [in] SMP N 7 White Land;Ground [of] School Year 2013 / 2014. Population in this research [of] student of SMP N 7 White Land;Ground [of] School Year 2013 / 2014. Sampel intake of research [is] 20 student of existing population. used [by] method [is] descriptive method. Technique analyse data used [by] normal curve and percentage. Effect of research sign that picture Motivate to have student achievement which have an affair [in] SMP N 7 White Land;Ground [of] School Year 2013 / 2014 can be seen from normal curve and percentage that low category ( 30%) Category [is] ( and high Category (0) Keyword:Motivasi have Achievement.